Effect of breathing exercises with biofeedback on blood pressure in pre-hypertensive women: a randomised controlled trial - Afaf M. Botla; Reham S. Ebrahim; Soheir M. Elkosery; Ahmed M. Darwesh; Dina M.A. Mohamed (Physiotherapy Quarterly)
Introduction Pre-hypertensive women are significantly more likely to develop hypertension or serious cardiovascular disease (CV). Autonomic nervous system abnormalities, such as sympathetic overactivity and parasympathetic withdrawal, are most likely the earliest functional changes in hypertension. The objective of this study was to determine the effect of breathing exercises with biofeedback on blood pressure (BP), heart rate variability (HRV), respiratory rate (RR), and skin galvanic response (SGR).